Da área de jogo à experiência do simbolizar: a fotografia como objeto de mediação na clínica do distúrbio psicossomático - Machado, Thais Duarte Luna (2020)
This current research aims to reflect on the effects of using photography as a mediation object in patients with a psychosomatic disorder, through the analysis of a clinical case. Winnicott’s contributions and the reference of the Photolanguage© method, as used by Claudine Vacheret, formed the base to develop this study. In order to achieve the specific goals, group psychoanalysis sessions which use photography as a mediation object with patients from the Somatization Studies and Therapy Program1, connected to the Psychiatry Department of the Federal University of São Paulo (UNIFESP), were analyzed. Concepts were identified and elaborated in order to create a reference and to promote the use of this device to understand, in the clinical case of one of the patients in the aforementioned group, how this mediation resource creates a potential space for a meeting with the sensorial, affective and motor experiences, which constitute engines for the symbolic processes. As for the methodology, the listening-research and the investigation with a view on the patient’s singularity were used, considering her insertion in the group and the multiple transferences at stake. The clinical fragments registered the patient’s path along one year and the analysis of this material used: 1) the analyst and researcher’s free-floating memory; 2) the session transcriptions, carried out by one of the group’s psychology interns; 3) the clinical discussions between the group’s two analysts; 4) the intersubjective elaborations in the institution’s supervision spaces. The study could point out that, through the use of photography as a mediation object in the group setting, the analyzed patient started to build a path towards the Me – Not Me separation, creating an ambivalence area without a big threat of losing some parts of herself. Moreover, the study showed that the photos worked as pictorial transitional objects towards language, allowing her to build a transitional space where the experiences could be supported, legitimated, intersected by the speech and gradually symbolized